State Compliance with the Recommendations/Decisions of the African Commission and the African Court on Human and Peoples’ Rights: A Critical Appraisal - Nkwiyir, Dr. Kwebe Augustine; Ray Junior, Dr. Akwe Ngole; Mokake, Mr. Fritz Lifoko (Law and Economy, 2026)
This study critically examines state compliance with the recommendations of the African Commission and the decisions of the African Court on Human and Peoples’ Rights, drawing on the Translational Legal Process Theory to analyze how legal norms are interpreted, internalized, and implemented within domestic contexts. The study assesses the binding nature of these decisions, identifies challenges that hinder implementation, and evaluates the practical effectiveness of the African human rights system. Employing a doctrinal research methodology, the study analyzes relevant treaties, protocols, case law, and scholarly literature to understand the factors inﬂuencing compliance. Findings reveal that compliance remains inconsistent and often partial, primarily due to political resistance, limited acceptance of the Court’s jurisdiction, weak regional enforcement mechanisms, domestic legal constraints, and reluctance to implement remedial measures. The study concludes that legal bindingness alone is insuﬃcient to guarantee compliance, emphasizing the importance of political will, domestic incorporation of judgments, and robust monitoring mechanisms. Recommendations include reaﬃrming state acceptance of the Court’s jurisdiction, strengthening African Union oversight, domesticating Court decisions, implementing capacity-building programs for oﬃcials, and fostering collaboration between the Commission and the Court. This study contributes to the discourse on human rights enforcement in Africa and provides practical strategies to enhance state accountability and the effectiveness of regional human rights institutions.